Energy dissipation in phase change salogels under shear stress. (22nd June 2022) - Karimineghlani, Parvin; Youssef, Abdelrahman A.; Benjamin, Chandler C.
Abstract: Phase change salogels are physical networks designed to shape stabilize salt hydrate phase change materials (PCMs) and inhibit the leakage of molten PCM. In contrast to chemically crosslinked gels, salogels can restructure by breaking of prior and reforming of new bonds. Therefore, salogels are susceptible to dissipate energy during deformations due to the nature of physical bonds. In the present work, different concentrations of diethylenetriamine, as a physical crosslinker, were added to a constant concentration of polyvinyl alcohol (PVA) in a high-salinity environment of a fluid inorganic PCM (lithium nitrate trihydrate), and network viscoelasticity was studied using oscillatory rheology. The energy dissipated was calculated by computing the area inside Lissajous stress-strain curves performed at various strain amplitudes and a constant frequency of 1 rad/s. The results of energy dissipation as a function of salogels' crosslinker concentration has a minimum when crosslinker concentration is ≅ 5–7 wt%. tes with the maximum point in the salogels' shear modulus graph. Lissajous plots' intracycle moduli analysis were used to quantify the observed non-linear behavior within a cycle of oscillation and proposed internal structure changes during deformation. Three regions based on the variation of dissipation energy with strain amplitudes ( γ ) for each salogel network were identified: region I ( γ < ∼10%): linear viscoelastic region, region II (∼10% < γ < ∼100%): intermediate strain region with shear thickening behavior and, region III ( γ > ∼100%): large deformation region with shear thinning behavior. Our results show that while most bonds are breaking at high strain amplitudes, there is a possibility of interchain reformation at intermediate shear strains due to the polymer chain alignment, which can slow down energy dissipation in this region. This study enhances the fundamental understanding of salogels' microstructural response to non-linear deformation, which would benefit energy storage applications subjected to large deformations such as conformable packs and pillows. Graphical abstract: Image 1 Highlights: Dissipation behavior of salogels was studied using non-linear rheology. Energy dissipation is strongly dependent on salogels crosslinker concentration. Variation of dissipation energy with strain amplitudes for each salogel network were identified. Salogels' interchain dynamic bond reformation at intermediate shear strains.